Effect of a fermented milk containing Bifidobacterium animalis DN‐173 010 on the health‐related quality of life and symptoms in irritable bowel syndrome in adults in primary care: a multicentre, randomized, double‐blind, controlled trial - GUYONNET, D.; CHASSANY, O.; DUCROTTE, P.; PICARD, C.; MOURET, M.; MERCIER, C.‐H.; MATUCHANSKY, C. (Alimentary Pharmacology and Therapeutics, 2007)
Summary Background  Health‐related quality of life (HRQoL) has been rarely evaluated as a primary endpoint in the assessment of the effect of probiotics on the irritable bowel syndrome (IBS). Aim  To study the effects of fermented milk containing Bifidobacterium animalis DN‐173 010 and yoghurt strains on the IBS in a multicentre, double‐blind, controlled trial. Methods  A total of 274 primary care adults with constipation‐predominant IBS (Rome II) were randomized to consume for 6 weeks either the test fermented milk or a heat‐treated yoghurt (control). HRQoL and digestive symptoms were assessed after 3 and 6 weeks on an intention‐to‐treat population of 267 subjects. Results  The HRQoL discomfort score, the primary endpoint, improved (P < 0.001) in both groups at weeks 3 and 6. The responder rate for the HRQoL discomfort score was higher (65.2 vs. 47.7%, P < 0.005), as was the decrease in bloating score [0.56 ± (s.d.)1.01 vs. 0.31 ± 0.87, P = 0.03], at week 3 in the test vs. the control group. In those subjects with <3 stools/week, stool frequency increased (P < 0.001) over 6 weeks in the test vs. control group. Conclusions  This study suggests a beneficial effect of a probiotic food on discomfort HRQoL score and bloating in constipation‐predominant IBS, and on stool frequency in subjects with <3 stools/week.